Gluten-free Bread Based on Tapioca Starch: Texture and Sensory Studies - Milde, Laura B. (2012)
In the present work, gluten-free formulations for breadmaking, destined to celiac people, were studied. A base blend of tapioca starch and corn flour (80:20) and typical bread ingredients such as yeast, salt, sugar and water were utilised. Ingredients such us vegetable fat, hen egg, and soybean flour were incorporated in different levels by means of an experimental design of three factors. Bread quality was analysed throughout physical (specific volume, weight loss percentage) and textural (firmness, elasticity and firmness recovery) parameters. The optimum bread selected, the bread with highest levels of fat and soybean flour and one egg, presented low values of firmness (≤100 N) and elasticity (>65%) and the lowest variation of these parameters with storage. Overall acceptability of this bread was 84% for habitual consumers of wheat bread and 100% by celiac people. Therefore, tapioca starch-based breads with spongy crumb, high volume and a good sensory acceptance were obtained.